EFFECT OF MANAGEMENT INFORMATION SYSTEM IMPLEMENTATION AND EMPLOYEE COMPETENCY ON EMPLOYEE PERFORMANCE PT. SUMEKAR - siti umyana (Universitas Trunojoyo Madura, 2022)
Employee productivity is one of the factors in improving services in an agency. This study aims to analyze the impact of implementing management information systems and employee qualifications on employee performance at PT. sumekar. In this study, data analysis used multiple linear regression analysis to measure the effect of more than one independent variable (independent variable) on the dependent variable (dependent variable), which was processed with SPSS based on the conceptual framework and identified hypotheses. to confirm some research hypotheses. The test results using regression analysis (beta test) on the dependent (y) and independent (X1) and (X2) variables indicate that the implementation of management information systems (X1) has a much stronger influence on employee performance (Y) when compared to the ability employees (X2). This is supported by the value calculation data for the implementation of management information systems (X1) which is greater than the ability of employees (X2). However, the combination of the two is able to make a significant contribution to employee performance.